Review Empowerment 21st Century Skills in Elementary School Science Learning through Need for Flipbook based Digital Teaching Materials - Zainulloh; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (PT FORMOSA CENDEKIA GLOBAL, 2022)
Strengthening efforts power competitive especially in the field source power man demand mastered skills life 21st century. Based teaching materials technology be one _ source necessary study _ developed for expedite the learning process. For that teaching materials used the digital aspect is necessary optimized. One of them with using flipbooks. Expected with competency flipbook _ student could developing, learning can fun and get studied anywhere student is at through internet network and gadgets. Study this aim for study need to development teaching materials with technology flipbook based for competency literacy read student could develop through science learning. Study done with use descriptive qualitative. Data collection techniques using questionnaire through google forms for study need flipbook -based teaching materials. Research results give information that the teacher still is use printed teaching materials available at the institution. The research results also show that the teacher has good commitment to opportunity development and utilization of flipbooks for means implementation digital teaching materials. Through results study this expected could motivating the teacher in choose development digital -based teaching materials through flipbooks for facilitate the learning process student